Social Security System of Elderly Population in Nepal - Bhandari, Kamala (NUTA Journal, 2019)
Population is classified as aging when older population become a proportionately larger share of the total population where as social security refers to the financial support action programme of Government intended to promote welfare of the population that is potentially directed to vulnerable segment of the society such as children, the elderly, the sick and the unemployed. It is the tool for the government to take care of well being of it's citizen. Population aging generates many challenges. In response to tackle these issues and to address their needs the Government has developed the social security policies, plan and acts. The main objective of this paper is to discuss on process of aging and the policy issue related to social security of old age population in Nepal. This paper follows descriptive and analytical method based on the secondary data. The data from these sources are used to analyze the trend and process of aging and social security system in Nepal. Furthermore this paper is based on review of literature mainly books, journal, article and report. Nepal is already in the process of population aging. population aging generates many challenges on social, economic and health care system. In response to tackle these issues and to address their needs the Government of Nepal has formulated separate policies and security programme for senior citizen and also committed to the various regional and international convention to promote welfare for senior citizen of the country.